2020
DOI: 10.1021/acscatal.0c03767
|View full text |Cite
|
Sign up to set email alerts
|

Artificial in Vitro Synthetic Enzymatic Biosystem for the One-Pot Sustainable Biomanufacturing of Glucosamine from Starch and Inorganic Ammonia

Abstract: Glucosamine is a naturally occurring bioactive amino monosaccharide which is widely used in the food, cosmetics, and pharmaceutical industries. It is traditionally produced by acid hydrolysis/enzymolysis of chitin but suffers from possible individual allergenic risk, serious environmental pollution, and low production yield. A recent rising approach for glucosamine production is microbial fermentation using engineered microorganisms to manufacture N-acetylglucosamine, followed by acid hydrolysis of N-acetylglu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 56 publications
0
18
0
Order By: Relevance
“…The C 1S spectrum (Figure d) was deconvoluted into three peaks: (i) 284.6 eV assigned to C–C and C–H bonds of sp 2 hybridization, (ii) 285.3 eV ascribed to C–O–C bonds, and (iii) 285.6 eV attributed to C–OH, CO, and O–C–O bonds, which further confirmed the presence of starch, the capping molecule . The N 1S spectrum (Figure e) exhibited two peaks at about 400.1 and 401.4 eV, which was ascribed with the amine group (C–NH 2 ) and protonated amine group (C–NH 3 + ) suggesting the interaction of starch and ammonia. , …”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…The C 1S spectrum (Figure d) was deconvoluted into three peaks: (i) 284.6 eV assigned to C–C and C–H bonds of sp 2 hybridization, (ii) 285.3 eV ascribed to C–O–C bonds, and (iii) 285.6 eV attributed to C–OH, CO, and O–C–O bonds, which further confirmed the presence of starch, the capping molecule . The N 1S spectrum (Figure e) exhibited two peaks at about 400.1 and 401.4 eV, which was ascribed with the amine group (C–NH 2 ) and protonated amine group (C–NH 3 + ) suggesting the interaction of starch and ammonia. , …”
Section: Resultsmentioning
confidence: 74%
“…The C 1S spectrum (Figure 4d 41 The N 1S spectrum (Figure 4e) exhibited two peaks at about 400.1 and 401.4 eV, which was ascribed with the amine group (C−NH 2 ) and protonated amine group (C−NH 3 + ) suggesting the interaction of starch and ammonia. 42,43 Under dark conditions, the catalytic activity of CuS NPs was evaluated for the degradation of sample dyes (MB, MO, and BB) with or without SO 3 2− . We observed that the CuS NPs/SO 3…”
Section: Resultsmentioning
confidence: 99%
“…Since some enzymes are not commercially available in present study, the cost for the lab scale production of enzyme is used first to estimate the cost for commercial ones. In a lab scale, enzyme cost of 1 kg substrate is about $12.7-14.4 (Meng et al, 2020;Han et al, 2020). Thus, we assume that the cost of enzyme in a lab scale in general is $20/kg substrate (higher than the value in literatures) and therefore commercially is $10/kg substrate.…”
Section: Estimation Of Variable Cost Ymentioning
confidence: 99%
“…This emerging biosystem for biomanufacturing features several advantages over in vivo systems (microbial fermentation), including fewer side reactions and easier adjustment of reaction conditions [2] and hence often result in high product yields and fast reaction rates [3][4][5][6]. Carbohydrates such as glucose, sucrose, cellobiose, cellulose, and starch are promising substrates for in vitro synthetic enzymatic biosystems to produce hydrogen [7][8][9], bioelectricity [10][11][12], and biochemicals such as myo-inositol [4,5,13], fructose 1,6diphosphate (FDP) [14], D-allulose [6], glucosamine [15], polyhydroxybutyrate [16], and monoterpenes [17]. The first step of these in vitro biosystems is the phosphorylation of carbohydrate substrates to either glucose 1-phosphate (G1P) or glucose 6-phosphate (G6P), which are two important intermediates for biosynthesis.…”
Section: Introductionmentioning
confidence: 99%